2013
DOI: 10.1089/neu.2012.2508
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Voltage-Gated Sodium Channel Nav1.3 Is Associated with Severity of Traumatic Brain Injury in Adult Rats

Abstract: During the secondary injury period after traumatic brain injury (TBI), depolarization of neurons mediated by voltagegated sodium channels (VGSCs) leads to cellular abnormalities and neurological dysfunction. Alterations in expression of different a subunits of VGSCs can affect early brain pathology following TBI. This study detected the expression of Nav1.3 mRNA and protein in the rat cortex post-TBI. Adult male Sprague-Dawley rats were randomly assigned to sham-TBI, mild-TBI (mTBI), or severe-TBI (sTBI) group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…Early studies also have demonstrated that a high anesthetic alcohol concentration inhibits sodium channel Nav1.3 91 , although lower alcohol levels, which occurs in chronic alcohol treatment, can promote adaptation by increasing its expression levels since the up-regulation of Nav1.3 is associated with traumatic brain injury severity in rats 92 . The other gene is vanilloid receptor TRPV1, a multimodal ion channel of afferent neurons that seems to play a role in hyperalgesia associated with inflammation 93 , 94 .…”
Section: Discussionmentioning
confidence: 99%
“…Early studies also have demonstrated that a high anesthetic alcohol concentration inhibits sodium channel Nav1.3 91 , although lower alcohol levels, which occurs in chronic alcohol treatment, can promote adaptation by increasing its expression levels since the up-regulation of Nav1.3 is associated with traumatic brain injury severity in rats 92 . The other gene is vanilloid receptor TRPV1, a multimodal ion channel of afferent neurons that seems to play a role in hyperalgesia associated with inflammation 93 , 94 .…”
Section: Discussionmentioning
confidence: 99%
“…The changes in AP and AHP amplitude are likely due to altered sodium and potassium channel densities and/or current amplitudes. Other models of TBI have been shown to alter current amplitude and expression of sodium and potassium channels (Dā€™Ambrosio et al, 1999 ; Hains et al, 2005 ; Lampert et al, 2006 ; Mao et al, 2010 ; Lei et al, 2012 ; Huang et al, 2013 ; Takahashi et al, 2013 ). The CypDKO reversed much of the increased membrane excitability induced by mTBI, including the AP and AHP amplitudes.…”
Section: Discussionmentioning
confidence: 99%
“…The findings corroborate a growing body of literature that underscores the importance of cytosolic sodium as a marker of tissue injury after trauma. In mTBI, twisting and stretching of axons results in mechanical disruption of membranes, altered function of voltage-gated sodium channels and sodium-potassium adenosine triphosphatase, 4,5,22 and changed regulation of the expression of sodium channels, 6,7 with potential persistent sodium abnormality.…”
Section: Discussionmentioning
confidence: 99%